Replacement of animal models of cardiac arrest and resuscitation strategies using a computer simulation - Daudre-Vignier, Clara (2024)
This doctoral thesis explores cardiac arrest (CA) and cardiopulmonary resuscitation (CPR) from a multidisciplinary perspective, with a focus on three main objectives: enhancing the Interdisciplinary Collaboration in Systems Medicine (ICSM) simulation suite, investigating the pathophysiology of CA, and proposing an alternative to animal models in CA and CPR research.